Simulations of relativistic jet formation in radio sources - Meier, D (2002)
Radio galaxies and quasars produce collimated, relativistic flows with. Lorentz factors of at least 15. It is generally believed that such flow Velocities indicate that jet acceleration and collimation occurs in the relativistic environment of a supermassive black hole. Recently, several groups around the world have begun to test theories of jet formation using magnetohydrodynamic (MHD) simulations of magnetized gas flow around black holes. This paper reviews the field of simulations of MHD jet formation, with an emphasis on producing the observed jet speeds and on the role that black hole angular momentum might play. Jet speeds are expected to be of order the escape velocity in the jet-formation region (bulk Lorentz factor similar to 2.4 if in the ergosphere of a rotating black hole), but could be potentially much higher if rapid acceleration can occur near the hole in less than a dynamical time. Transient simulations often produce tightly-collimated jets, but in a steady state jet collimation is generally quite slow and broad. Regardless of the source of the rotational energy powering the jet (accretion disc or black hole spin), the total jet power should be proportional to the black hole mass and the accretion rate. When the type of accretion disc is taken into account, it is shown that the most powerful jets should occur when the black hole is rotating rapidly and when the accretion disc is geometrically. thick and hot. The implications of this modified spin paradigm for explaining phenomenological properties of both supermassive and stellar mass black hole systems is discussed.